Perancangan Sistem Informasi Permohonan Cuti Karyawan Menggunakan Metode Unified Software Development Process (USDP) (Studi Kasus: PT. Safe And Secure Guarding) - Azmi Muslimah Madaniah; Rinna Rachmatika (CV. Multi Kreasi Media, 2022)
PT Safe and Secure Guarding is an outsourcing company with a business focus on providing security services, cleaning services, parking, and the application of security equipment and has a total of approximately 600 employees spread across the head office and other areas. The leave application process requires each employee to submit an application on a leave form on a paper provided by HRD which is addressed to each field coordinator a maximum of 3 days before the leave is executed and approved by the field coordinator and HRD. Likewise, for employees who are undergoing Work from Home (WFH) or employees who work at home, the employee needs to report himself to make absences like applying for leave. All leave requests will be recorded by HRD in a file box. This process has problems, including the process of submitting leave that still uses paper, which is prone to data loss due to lost paper or tucked between several existing documents. The submission process that must be submitted directly by employees makes the submission process take a long time because the leave validation process from each division cannot be carried out quickly. For some employees who need sudden leave or permission, it is difficult to do because the leave application process cannot be done anywhere. In addition, the leave data recap stored in the file box makes the process of searching for leave data difficult and takes a long time. The process design method is focused on model development using UML (Unified Model Language) and using the PHP programming language, as well as Xampp v3.2.2 with Apache as the web server and MySQL as database storage. This study resulted in an application that was able to record all employee leave data to minimize data loss that could occur on the current system, make it easier for employees to process leave applications that can be done anywhere and anytime and speed up the process of searching for employee leave application data. which has existed.